Gender and Christian Spirituality in Africa: A Ghanaian Perspective - Amenga-Etego, Rose M. (Black Theology: An International Journal, 2012)
Questions surrounding gender and Christian spirituality in Ghana generally produce answers that seek to suggest that there are no gender-based differences or problems on the issue. Yet, unlike that which can be deciphered from existing literature, other sources such as in-depth interviews on real life circumstances and a critical examination of the responses given, seem to present a different picture of the situation on the ground. This continues to bring to the fore the differences between theory and praxis, particularly on issues concerningwomcn in Africa. Using examples from indigenous Akan and Nankani spiritualities, this article examines the nature and history ofgendcr and Christian spirituality in Africa with excerpts from some of the works of Mercy Amba Oduyoye, the first and most renowned Ghanaian female theologian.
free
Keywords: CHRISTIANITY & gender; GHANA; Gender; Ghana; ODUYOYE; Mercy Amba; RELIGIOUS life of women; SPIRITUALITY; spirituality